PERBANDINGAN MEMANDIKAN TRADISIONAL DENGAN DISPOSABLE BED BATHS DI RUANG INTENSIVE CARE UNIT (ICU): Comparison Between Traditional Bathing And Disposable Bed Baths In Intensive Care Unit (ICU) - Muhammad Yusuf; Yuliana Syam; Andi Masyita Irwan (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2019)
Introduction: Approximately 1.75 to 3.5 million patients in the hospital get nosocomial infection each year. Patients in ICU that mechanically installed ventilators is unable to meet the needs of self-care, bathing. Bathing with Disposable bed baths (DBB) method using disposable bath wash lap can reduce the time in bathing and eliminating the use of bath basin that proved as a reservoir for bacteria and can transmit infection in hospital. This study aims to compare the duration, cost and differences in the number of microorganisms between traditional bathing and using Disposable Bed Baths. Method: The literature search used four databases: Pubmed, ProQuest, Science Direct, and Google Scholar by including traditional bathing keywords, Disposable bed baths, with year-end published in 2011 to 2017. This study obtained 34 articles with exclusions 22 articles. Result: Articles that are relevant to the topic are 12 (2 systematic review, 1 descriptive study, 5 randomized controlled trials, 4 case study). Setting of patient research in ICU and having elderly patient. Some research finds that both bathing methods can reduce the number of microorganisms in the skin, traditional bathing can cause dry skin. In terms of cost and bathing duration, bathing methods with disposable bed baths better than traditional bathing methods. Conclusions: There is little research on the comparison of traditional bathing and disposable bed baths in relation to cost, duration and number of microorganisms, especially patients treated in the ICU. Key words : traditional bathing, disposable bed baths, ICU